Environmental externalities caused by urbanization in the city of Medellín - Palmett Plata, Olgalicia (Corporación Universitaria del Caribe, CECAR., 2016)
Abstract: This paper aims to reflect on how, in the city of Medellín, environmental externalities, caused by the dynamics of urbanization, have been faced in the decades between 1990 and 2010. As a result, we seek to know and contribute to the new improvement actions implemented in Medellín, to counteract the environmental externalities caused by urbanization, by using the proper characteristics of a particular context, such as, in the case of the city of Medellín, a strategic geographical location, a singular relief, social conflicts of a known particularity, entrenched cultural traditions and reduced economic possibilities, among others. In addition, it seeks to reveal and strengthen the articulations that have been strategically established in urban environmental management policies and the achievements in view of the fundamental principles (1, 8 and 26) of the Rio de Janeiro Summit (1992), before the environmental externalities in the city and that can be assumed as a model of action for territories with similar behaviors.___Keywords: City, environmental externalities, urbanization, affectations. ___Resumen: Este trabajo tiene como objetivo realizar una reflexión sobre la forma cómo, en la ciudad de Medellín, se han enfrentado las externalidades ambientales, ocasionadas por las dinámicas de urbanización, en las décadas entre 1990 y 2010. Se busca como resultado conocer y aportar las nuevas acciones de mejoramiento implementadas en Medellín, para contrarrestar las externalidades ambientales ocasionadas por la urbanización, a la luz del aprovechamiento de características propias de un contexto, como son, en el caso de la ciudad de Medellín, una ubicación geográfica estratégica, relieve singular, conflictos sociales de conocida particularidad, tradiciones culturales arraigadas y posibilidades económicas reducidas, entre otras. Además, se pretende revelar y potenciar las articulaciones que estratégicamente se han ido constituyendo en las políticas de gestión ambiental urbana y los logros obtenidos ante los principios fundamentales (1, 8 y 26) de la Cumbre de Río de Janeiro (1992), ante las externalidades ambientales en la ciudad y que pueden ser asumidos como modelo de actuación para territorios con comportamientos similares. ___Palabras clave: Ciudad, externalidades ambientales, urbanización, afectaciones. ___Recibido: 30 de marzo de 2016. Aceptado: 19 de mayo de 2016.